Gas Sensing Properties and Mechanism of Nano-SnO2-Based Sensor for Hydrogen and Carbon Monoxide. (4th December 2012) - Chen, Weigen; Zhou, Qu; Wan, Fu; Gao, Tuoyu
Abstract : Nano-SnO2 powder was prepared by the hydrothermal method in this paper. X-ray powder diffraction (XRD) and scanning electron microscopy (SEM) were used to characterize the composition of the crystalline phase and the morphology of the prepared gas-sensitive materials, respectively. In particular, the study focused on the sensing behaviors of nano-SnO2 -based sensor towards power transformer fault gases such as hydrogen and carbon monoxide. The optimum working temperature for hydrogen and carbon monoxide is about 400 ∘ C and 360 ∘ C, separately. Further investigations into the adsorption process of gas molecule on SnO2 (110) surface based on the first principles were conducted. The calculations indicated that 1 σ orbits of H2 split into several new electronic peaks and 5 σ orbits of CO almost degenerated completely in the adsorption process, which promoted charge transfer between gas molecule and SnO2 (110) surface. It provides a qualitative explanation for the prepared nano-SnO2 -based sensor exhibiting different gas sensing properties towards H2 and CO.